Quantitative risk assessment of listeriosis from traditional brazilian minas artisanal semi-hard and fresh soft cheeses - Campagnollo, Fernanda B. (2019)
Traditional Minas cheeses are very popular in Brazil. These cheeses are of two types: artisanal ripened semi-hard cheeses (HC) produced with raw milk and refrigerated fresh soft cheeses (SC) generally produced with pasteurized milk. Purpose: This study estimates the risk of listeriosis due to HC and SC consumption using quantitative microbial risk assessment (QMRA). Methods: QMRAs were developed for both cheese types. The HC model contained a module for predicting Listeria monocytogenes decline during ripening. The SC model contained a refrigerated storage module for predicting L. monocytogenes growth during storage. HC modeling scenarios varied L. monocytogenes starting concentration over -2.4 to 6 log CFU/ml in raw milk and three ripening times (4, 22, and 60 days). SC modeling scenarios varied L. monocytogenes starting concentration (-2.4 to 4 log CFU/ml in milk). Inclusion of antilisterial lactic acid bacteria (LAB) was also examined. Simulations (100,000 iterations per scenario) were carried out using the @Risk add-in for Excel. Results: Aging HC reduced risk, and risk was influenced by L. monocytogenes starting concentration. Aging 22 days with inhibitory LAB reduced risk more than 4 million-fold when L. monocytogenes was assumed to be 6 log CFU/ml in raw milk, and was lower risk than HC made without LAB and with a starting concentration of 1 log CFU/ml in raw milk. Inclusion of inhibitory LAB reduced risk of listeriosis from SC, but not as dramatically as for HC. Relative risk to vulnerable populations reduced 4.4 and 3.4-fold when L. monocytogenes starting concentrations were 1 log and 4 log CFU/ml in milk, respectively. Significance: The results of the QMRA predict that consumption of contaminated Minas cheeses can present a high risk of listeriosis, especially for vulnerable populations. Scenario analyses indicate that aging of HC and inclusion of LAB in HC and SC are effective risk mitigation measures.